منهج الحافظ ابن حجر في نقده لحتون السنة من خلال كتابه "فتح الباري شرح صحيح البخاري - Majed Mohammad Rafea Al Juhani (Universiti Sains Islam Malaysia, 2024)
This study investigates Ibn Ḥajar al-ʿAsqalānī’s Approach in criticizing the Mutun of Sunnah (it is the plural form of Matin، containing the substance of the prophet’s sayings in his book “Fath al-Bari: Sharah Sahih Al-Bukhari ”. Ibn Hajar spoke about the science of criticism of Matin and its developmental stages until the late centuries and spoke about the most essential critical criteria used by scholars in investigating Matin. The study has also investigated the negative and positive aspects of Ibn Hajar’s approach of criticism. The study has adopted inductive analytical research. The study concludes that Ibn Hajar was very objective and sincere in criticizing Mutun. Although Ibn Hajar criticized some utterances and topics in Sahih al-Bukhari، he was very careful to maintain the authenticity and originality of the authentic Hadith free from any criticism، not based on reliable criteria. The study also demonstrates the main criteria used by Ibn Hajar in criticizing Matin. To be authentic and reliable in his criticism، Ibn Hajar used and relied on different authentic sources such as the Holy Quran، authentic Hadith، historical incidents، grammar of Arabic language، Arab literature، sound logic and well-known scholars.